Parmalat USA turnaround - Shein, James B., 1942-; Haines, Nathan; Horstmann, Matthew; Kaulfus, Tobias; Koester, Craig; Koo, William; Landin, Juan Lariz (London : Kellogg School of Management, 2008)
The case explains the financial fraud committed by Parmalat and the measures used by Paramalat USA (a milk bottler and supplier) to turn the company around and prevent the company being sold off at a huge loss for its creditors.
Originally published in Shein, J. B., Haines, N., Horstmann, M., Kaulfus, T., Koester, C., Koo, W., & Landin, J. L. (2008). Parmalat USA turnaround. 5-208-253. Evanston, IL: Kellogg School of Management at Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Parmalat (Firm) -- Case studies; Corporations -- Corrupt practices -- United States -- Case studies; Fraud -- United States -- Case studies